2014
DOI: 10.11646/zootaxa.3869.1.8
|View full text |Cite
|
Sign up to set email alerts
|

On the identity of Trichogramma demoraesi Nagaraja (Hymenoptera: Trichogrammatidae), with a checklist and a key to Trichogramma species associated with Erinnyis ello (L.) (Lepidoptera, Sphingidae) in Brazil

Abstract: Specimens collected from eggs of the cassava hornworm Erinnyis ello, originally identified as T. demoraesi, were compared with the paratype of this species. Based on morphological analysis, the specimens from E. ello actually belong to Trichogramma marandobai Brun, Moraes and Soares, 1986. Therefore, T. demoraesi is not a parasitoid of the eggs of E. ello, a major pest of cassava. The main features separating the two species, and a checklist and key to the species of Trichogramma associated with E. ello are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Trichogramma demoraesi was erroneously identified in Brazil as a parasitoid of Erinyis ello, a major pest of cassava. Examination of the paratype of T. demoraesi revealed that it was misidentified and actually corresponds to T. marandobai (Vieira et al 2014). Therefore, T. demoraesi does not parasitize E. ello in Brazil (Vieira et al 2014), and all records on that host previous 2014 are misidentifications.…”
Section: Trichogramma Demoraesimentioning
confidence: 99%
See 4 more Smart Citations
“…Trichogramma demoraesi was erroneously identified in Brazil as a parasitoid of Erinyis ello, a major pest of cassava. Examination of the paratype of T. demoraesi revealed that it was misidentified and actually corresponds to T. marandobai (Vieira et al 2014). Therefore, T. demoraesi does not parasitize E. ello in Brazil (Vieira et al 2014), and all records on that host previous 2014 are misidentifications.…”
Section: Trichogramma Demoraesimentioning
confidence: 99%
“…Examination of the paratype of T. demoraesi revealed that it was misidentified and actually corresponds to T. marandobai (Vieira et al 2014). Therefore, T. demoraesi does not parasitize E. ello in Brazil (Vieira et al 2014), and all records on that host previous 2014 are misidentifications. The most conspicuous character to separate these species is the dorsal lamina, which is narrow at the base and fork-shaped in T. demoraesi, and broader and not fork-shaped in T. marandobai.…”
Section: Trichogramma Demoraesimentioning
confidence: 99%
See 3 more Smart Citations